Lies my preacher told me: an honest look at the Old Testament - Strawn, Brent A. (Presbyterian Publishing Corporation, 2021)
In this concise volume, Brent Strawn addresses ten common "lies" or mistruths about the Old Testament, from perceptions of God's personality (the "angry Old Testament God") to the relevance of the Old Testament for Christians. Designed for easy reading and group discussion, this book will expand your thinking about the Bible's First Testament.